Re-examination of the reciprocal relation between intrinsic motivation and competence beliefs in math using the random-intercept cross-lagged panel framework - Paschke, Patrick; Steinmayr, Ricarda; Mertens, Alica; Neubauer, Andreas B.; Spinath, Birgit (Child development, 2025)
Previous studies employing cross-lagged panel models (CLPMs) found mixed results regarding reciprocal relations between competence beliefs and intrinsic motivation. CLPMs have been criticized for leading to erroneous causal inference in certain situations. Two datasets were analyzed regarding reciprocal relations between competence beliefs and intrinsic motivation with the alternative random-intercept cross-laged panel models (RI-CLPMs). One dataset contained 670 2nd to 3rd grade students (M = 8.80 years old, 98% white, 55.7% female) and the second dataset contained 542 2nd to 4th grade students (M = 7.96 years old, 76.7% native German speakers, no information on ethnicity, 50.2% female) in Germany. The results revealed little to no evidence for reciprocal relations between the constructs.